Ultrasonic-assisted wound debridement: report from a closed panel meeting. (2nd February 2020) - Swanson, Terry; Lázaro-Martínez, José Luis; Braumann, Chris; Kirchhoff, Jan-Birger; Gächter, Bernd; van Acker, Kristien
Abstract : Mechanical debridement can be considered as an alternative to surgical debridement if surgery is not available, or is considered impractical or too high risk. One form of selective mechanical debridement is ultrasonic-assisted wound (UAW) debridement. As the published evidence on this is limited, a closed international expert meeting was held to review the existing evidence base on it, present preliminary findings of research currently in progress and discuss individual cases selected from the clinical experts' own practice. The panel also explored the potential barriers to the implementation of UAW debridement and how these might be addressed. It concluded there is sufficient evidence that UAW debridement is an effective method of cleansing and debriding almost all hard-to-heal wounds. Patients who are most likely to benefit from it are not medically stable, on anticoagulants, unable to visit a hospital for wound treatment, and/or have wounds with a poor vascular supply or are close to critical structures. The panel also observed that UAW debridement can be used to prepare the wound for negative pressure wound therapy (NPWT) or as an adjunctive to it. Given the potential to experience pain during the procedure, the panel considered that patients will benefit from topical analgesia. The panel noted that health professionals, patients and visitors must be protected from the aerosolisation associated with UAW, to reduce risk of cross-contamination.